Canonical Transient Receptor Potential Channels and Vascular Smooth Muscle Cell Plasticity - Motohiro Nishida; Tomohiro Tanaka; Supachoke Mangmool; Kazuhiro Nishiyama; Akiyuki Nishimura (The Korean Society of Lipid and Atherosclerosis, 2020)
Vascular smooth muscle cells (VSMCs) play a pivotal role in the stability and tonic regulation of vascular homeostasis. VSMCs can switch back and forth between highly proliferative (synthetic) and fully differentiated (contractile) phenotypes in response to changes in the vessel environment. Abnormal phenotypic switching of VSMCs is a distinctive characteristic of vascular disorders, including atherosclerosis, pulmonary hypertension, stroke, and peripheral artery disease; however, how the control of VSMC phenotypic switching is dysregulated under pathological conditions remains obscure. Canonical transient receptor potential (TRPC) channels have attracted attention as a key regulator of pathological phenotype switching in VSMCs. Several TRPC subfamily member proteins-especially TRPC1 and TRPC6-are upregulated in pathological VSMCs, and pharmacological inhibition of TRPC channel activity has been reported to improve hypertensive vascular remodeling in rodents. This review summarizes the current understanding of the role of TRPC channels in cardiovascular plasticity, including our recent finding that TRPC6 participates in aberrant VSMC phenotype switching under ischemic conditions, and discusses the therapeutic potential of TRPC channels.